Effect of partial replacement of soybean meal with jackbean (Canavalia ensiformis) as an alternative plant protein in the practical diets of cat fish (Clarias gariepinus) (2015)
This study assessed the potentials of Jackbean seed meal (JBSM) for partial replacement of soybean in diets of Clarias gariepinus. Hence, five diets were formulated at 40% crude protein level as Soybean in control diet (CD) was replaced progressively at (5%, 10%, 15% and 20%) by JBSM in test diets TD1, TD2, TD3, TD 4 respectively. The Jackbean seeds were treated by dehulling, soaking in ash and followed by boiling to reduce the anti nutritional content (canavanine) present in the seeds. Fifteen plastic tanks of (37 liters) containing 25 liters of water was used for growth trial. Each treatment contained 15 fingerlings with an average weight of 6.44 ± 0.1g in three replicates per treatment. Test fish in each tank were fed 5% of their biomass twice daily for 84days. At the end of the experiment proximate composition and growth parameters were analyzed. Result showed that fish fed TD 1 (5% inclusion level) and TD2 (10% inclusion level) compared favourably with the control diet (P ? 0.05). Fish fed control diet had the best specific growth rate (0.54) and feed efficiencies (Protein Efficiency Ratio (PER)= 0.41 and (Food Conversion Ratio, FCR= 6.57). However, considering the results of the statistical analysis used to compare the difference between the means of the different treatment, TD1 (5% inclusion level) compared most favourable with the control in terms of mean weight gain (8.87), specific growth rate (0.39) which was significantly different (P ? 0.05) from other treatments, PER from CD, TD3 and TD4 which are not significantly different (P ? 0.05) from TD2, and FCR (9.41) which was not significantly different (P ? 0.05) from CD but significantly different (P ? 0.05) from TD2, TD3 and TD4. From the results of this study, it shows that 5% of soybean in the diet can be replaced with JBMS without any adverse effect on the growth performance.